Close focus : interpreting Western Australia’s visual culture - Snell, Edgar William (Curtin University, 2011)
Distance from the centres of world art and from national hubs of creative practice provides both opportunities and constraints for Western Australian visual artists. Informed but isolated, they have learned to direct the lens shaped by received ideas onto the extraordinary natural environment they inhabit. Regional perspectives influence this act of re-focusing, which is inflected by local knowledge and personal experience in a process of reinvention and re-imagination that has escalated since the Second World War.The objective of this PhD by supplication is to situate my practice as an art historian, critic and curator within the broader context of Australian visual culture and to examine how the process of assimilation, described by George Seddon as taking 'imaginative possession', has contributed to our understanding of local identity within the wider framework of a national identity.In my writing and through my activity as a curator of exhibitions over the past two decades, I have identified the importance of local conditions in generating a critical, regional practice and I have shown how imported ideas have been absorbed, modified and accommodated within the work of the State’s leading artists to create a vibrant sense of regional identity that makes a significant contribution to our understanding of a wider and more comprehensive view of cultural practice in Australia.